Polymethoxyflavones extracted from Bauhinia championii alleviate LPS-induced acute lung injury by ameliorating endoplasmic reticulum stress - Li, Yuanyuan; Yang, Xiaolan; Ye, Wenjing; Jing, Junsong; Chen, Ranran; Wu, Lianhao; You, Zhenqiang; Zhang, Sheng; Shi, Jing (Frontiers in Pharmacology, 2025)
BackgroundAcute lung injury (ALI), a critical respiratory condition, often escalates into acute respiratory distress syndrome, which is associated with significant morbidity and mortality. Bauhinia championii, a botanical drug used in traditional Chinese medicine, is reputed for its antioxidative and anti-hypoxia effects. However, the active metabolites within B. championii and their mechanisms of action in alleviating ALI remain to be elucidated.MethodsA comprehensive literature review and database search within Chemistry Database were conducted to compile a complete profile of the metabolites identified in B. championii. Utilizing network analysis, we predicted potential targets of metabolites in B. championii (MBC) for ALI treatment. A protein-protein interaction (PPI) network was constructed using Cytoscape 3. 9. 1, complemented by GO annotations and KEGG pathway enrichment analyses via the DAVID online platform. The isolation and characterization of polymethoxyflavones (PMFs) from B. championii were performed using HPLC and confirmed by LC-MS. In vivo pharmacological assessments were executed to substantiate the network analysis predictions. Moreover, the Autodock software facilitated molecular docking studies to elucidate the role of endoplasmic reticulum (ER) stress modulation in ALI treatment by PMFs.Results17 known MBC were identified in which 7 active metabolites of flavonoids were used as predictive targets. 122 target genes associated with both MBC and ALI were tested for KEGG and GO enrichment analyses, which indicated these target genes involvement in antioxidant, anti-inflammatory, and anti-apoptotic pathways. The PMFs were extracted from B. championii and identified as 5, 6, 7, 3′, 4′-pentamethoxyflavone, 5, 6, 7, 3′, 4′, 5′-hexamethoxyflavone, 5, 7, 3′, 4′, 5′-pentamethoxyflavone, 5, 6, 7, 5′-tetramethoxy-3′, 4′-methylenedioxyflavone and 5, 7, 5′-trimethoxy-3′, 4′-methylenedioxyflavone. PMFs were effective in alleviating LPS-induced pulmonary inflammatory responses for releasing ALI. In addition, PMFs inhibited the secretion of GSH-Px and CAT, reduced the accumulation of HYP and MDA as well as the infiltration of inflammatory cells, not to mention alleviated LPS-induced apoptosis by inhibiting the Caspase 3-mediated apoptosis pathway. Furthermore, the PMFs can spontaneously bind to multiple ER stress targets to exert the effect of calming ER stress to alleviate ALI.ConclusionPMFs inhibited the expression of inflammatory cytokines and reduced oxidative stress injury to resist apoptosis in lung. Moreover, PMFs attenuated LPS-induced ER stress activation by regulating ER stress related targets, which in turn alleviated ALI.